Metaforis dalam Lirik Lagu Populer Bertemakan Percintaan - Hermintoyo, Muhamad (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
AbstractThe lyrics of the song are like the poetry of an aesthetic element that builds them as intrinsic elements, such as diction, rhyme, images and rhetorical means. In the hands of creative authors will create an interesting private diction diction and bring up beautiful metaphors. Song lyrics are created based on the author's emotional expression both from personal experience and see around him as the object of his creation. One of the most widely made is the lyrics of the song with the theme of romance, both ranging from approach / introduction, romantic seduction to the sadness left by her lover. This article discusses the metaphorical phrases in the lyrics of popular songs with the study of aesthetics, the elements that build the lyrics and their meaning. IntisariLirik lagu tak ubahnya seperti puisi ada unsur estetis yang membangunnya berupa unsur intrinsiknya, seperti diksi, rima , imaji dan sarana retorika. Di tangan pengarang yang kreatif akan memunculkan diksi private symbol yang menarik dan memunculkan metafor-metafor yang indah. Lirik lagu diciptakan berdasar ekspresi emosional pengarangnya baik dari pengalaman pribadi maupun melihat di sekitarnya sebagai objek penciptaannya. Salah satu yang paling banyak dibuat adalah lirik lagu yang bertemakan percintaan, baik mulai dari pendekatan/pengenalan, rayuan romantisnya sampai pada kesedihan ditinggal kekasihnya. Artikel ini membahas kalimat-kalimat metaforis dalam lirik lagu populer dengan kajian estetikanya, yaitu unsur yang membangun lirik dan maknanya.